Alteration of protein expression pattern of vascular endothelial growth factor (VEGF) from soluble to cell-associated isoform during tumourigenesis - Cressey R. (2014)
Background: Vascular endothelial growth factor (VEGF) is a potent mitogen for endothelial cells, and its expression has been correlated with increased tumour angiogenesis. Although numerous publications dealing with the measurement of circulating VEGF for diagnostic and therapeutic monitoring have been published, the relationship between the production of tissue VEGF and its concentration in blood is still unclear. The aims of this study were to determine: 1) The expression pattern of VEGF isoforms at the protein level in colorectal and lung adenocarcinoma in comparison to the pattern in corresponding adjacent normal tissues 2) The relationship between the expression pattern of VEGF and total level of circulating VEGF in the blood to clarify whether the results of measuring circulating VEGF can be used to predict VEGF expression in tumour tissues. Methods: Ninety-four tissue samples were obtained from patients, 76 colorectal tumour tissues and 18 lung tumour tissues. VEGF protein expression pattern and total circulating VEGF were examined using western blot and capture ELISA, respectively. Results: Three major protein bands were predominately detected in tumour samples with an apparent molecular mass under reducing conditions of 18, 23 and 26 kDa. The 18 kDa VEGF protein was expressed equally in both normal and colorectal tumour tissues and predominately expressed in normal tissues of lung, whereas the 23 and 26 kDa protein was only detected at higher levels in tumour tissues. The 18, 23 and 26 kDa proteins are believed to represent the VEGF121, the VEGF165 and the VEGF189, respectively. There was a significant correlation of the expression of VEGF165 with a smaller tumour size maximum diameter <5cm (p<0.05), and there was a significant correlation of VEGF189 with advanced clinical stage of colorectal tumours. The measurement of total circulating VEGF in serum revealed that cancer patients significantly (p<0.001) possessed a higher level of circulating VEGF (1081±652 pg/ml in colorectal and 1,251±568 pg/ml in lung) than a healthy volunteer group (543±344 pg/ml). No correlation between the level of circulating VEGF and the pathologic features of tumours was observed. Conclusions: Our findings indicate that the expression patterns of VEGF isoforms are altered during tumourigenesis as certain isoform overexpression in tumour tissues correlated with tumour progression indicating their important role in tumour development. However, measurement of VEGF in the circulation as a prognostic marker needs to be carefully evaluated as the cell-associated isoform (VEGF189), but not the soluble isoform (VEGF121 and VEGF165) appears to play important role in tumour progression. © 2005 Cressey et al., licensee BioMed Central Ltd.